   SEARCH HOME Math Central Quandaries & Queries  Question from amber, a student: Please help me with this problem x+y=-2 y-2x=1 Hi Amber,

I'm going to illustrate with a different problem.

Solve the equations
y - x = 3
x + 2y = 3

I am going to use the substitution method so I want to solve one of the equations for one of the variables. I'm going to solve the first equation for y. If you add x to both sides of the first equation equation you get

y = x + 3

Now the substitution step, substitute y = x + 3 into the second equation

x + 2(x + 3) = 3

Now I have one equation in one unknown which I can solve

x + 2(x + 3) = 3
x + 2x + 6 = 3
3x + 6 = 3
3x = 3 - 6 = -3
x = -1.

To find y substitute x = -1 into either of the equations I started with. The first equation looks the easiest so

y - x = 3
y - (-1) = 3
y + 1 = 3
y = 3 - 1 = 2.

Thus my answer is x = -1, y = 2. (I checked by substituting these values into both equations to ensure that my answer was correct.)

Now use the same method to solve the equations you sent us.

Penny     Math Central is supported by the University of Regina and The Pacific Institute for the Mathematical Sciences.